How do referees visually explore? An in-situ examination of the referential head and eye movements of football referees - Van Biemen, T.; Mann, D. L. (Journal of Sports Sciences, 2024)
The majority of a football referee`s time is spent assessing open-play situations, yet little is known about how referees search for information during this uninterrupted play. The aim of the current study was to examine the exploratory gaze behaviour of elite and sub-elite football referees in open-play game situations. Four elite (i.e. national) and eight sub-elite (i.e. regional) referees officiated an in-situ football match while wearing a mobile eye-tracker to assess their gaze behaviour. Both referential head and eye movements (i.e. moving gaze away from and then back to the ball) were measured. Results showed gaze behaviour was characterised overall by more referential head than eye movements (~75 vs 25%), which were of longer duration (~950 vs 460 ms). Moreover, elite referees employed faster referential movements (~640 vs 730 ms), spending less time with their gaze away from the ball (carrier) than the sub-elite referees. Crucially, both the referential head and eye movements were coordinated relative to key events in the match, in this case passes, showing that referees anticipate the passes to ensure that the referential movements did not occur during passes, rather before or after. The results further our understanding of the coordinative gaze behaviours that underpin expertise in officiating.